Anarchokapitalistyczna koncepcja bezpieczeństwa jednostki - Matuszek, Krzysztof (Polityka i Społeczeństwo, 2020)
The aim of this article is to attempt to present and evaluate the conception of human security, proposed by anarcho-capitalism – a radical trend of libertarianism. The content analysis method was used to realize this task, while the main source of works constitutes the main works of the leading anarcho-capitalists: Murray Newton Rothbard, David Friedman and Hans-Hermann Hoppe. The results of the work is the adoption of several conclusions, including, first of all, that the anarcho-capitalist conception of human security is undoubtedly an innovate idea, contesting commonly recognized solutions in this matter.